The Changing of Environmental Approval Administrative Law Perspective - Fitri Nur Aini Prasetyo; Abdul Kadir Jaelani (Journal of Human Rights, Culture and Legal System, 2022)
The renaming of environmental permits to environmental agreements is one of the issues highlighted by the Job Creation Law. Environmental approvals were deemed to not meet the licensing requirements of the State Administrative Law, so they could potentially not be challenged in court like environmental permits. This change prompted opposition from various groups. The purpose of this study is to identify the characteristics of environmental approval from the standpoint of State Administrative Law. This is normative law (doctrinal) research with a statutory and a conceptual approach (conceptual approach). Environmental approvals in the Job Creation Law can be classified as permits under State Administrative Law, and environmental approvals are granted to business actors, according to the findings of this study.